Dosage compensation of the mammalian X chromosome influences the phenotypic variability of X-linked dominant male-lethal disorders. Issue 7 (7th May 2008) - Morleo, M; Franco, B
Abstract : In mammals females inactivate one of the two X chromosomes during early development to achieve an equal gene dosage between sexes. This process, named X chromosome inactivation (XCI), usually occurs randomly. However, in a few instances, non-random XCI may take place, thus modulating the phenotype observed in female patients carrying mutations in X-linked genes. Different aspects related to dosage compensation contribute to explain the influences of XCI on the phenotypic variability observed in female patients. The study of two X-linked dominant male-lethal disorders, such as the microphthalmia with linear skin lesions (MLS) syndrome and the oral–facial–digital type I (OFDI) syndrome, offers the opportunity to discuss this intriguing topic. In addition, recent data on the characterisation of a murine model for OFDI provide the opportunity to discuss how differences in the XCI between Homo sapiens and Mus musculus can justify the discrepancies between the phenotypes observed in OFDI patients and the corresponding murine model.